Intervenciones de enfermería en prevención de anafilaxia post transfusión transoperatoria de hemoderivados: revisión sistemática - Chicaiza Rosero, Diego Fernando (2025)
Transfusion of perioperative blood products is a risky activity due to the possibility of anaphylactic reactions. The objective of this study was to describe nursing interventions to prevent anaphylaxis after intraoperative transfusion of blood products through a systematic review. A qualitative and descriptive methodology was used in bibliographic reviews. A search was conducted in scientific databases and institutional repositories to identify 80 articles related to anaphylactic reaction due to transfusion of perioperative blood products. Inclusion and exclusion criteria were applied, a systematic extraction of relevant data was performed, and a critical analysis of the methodological quality of the included studies was carried out. Screening analysis of the articles resulted in the inclusion of 20 studies in the final review. The results indicated nursing activities necessary for proper administration of perioperative blood products, as well as signs and symptoms present in anaphylaxis. Scientific evidence supports a low occurrence of post-transfusion anaphylaxis, indicating the need for adequate administration, staff preparation, and measures that can be taken if the problem arises. It is concluded that the training of health professionals, both in nursing and medicine, plays an important role in protecting the patient's integrity. Consider correctly filling out forms from the beginning of the transfusion to the end. Overcoming these challenges requires a comprehensive approach that includes appropriate training to ensure patient well-being and be prepared for any eventuality.